Golden Gater 7 April 1964 - San Francisco State University - Associated Students:::::: (San Francisco State University - Associated Students, 1964)
This was a publication of the San Francisco State University English Department and Associated Students from 1922 to 1969. The Journalism Department then took over production of the paper from 1969 to the present.